2011
DOI: 10.1534/genetics.111.128322
|View full text |Cite
|
Sign up to set email alerts
|

The Hog1 Mitogen-Activated Protein Kinase Mediates a Hypoxic Response inSaccharomyces cerevisiae

Abstract: We have studied hypoxic induction of transcription by studying the seripauperin (PAU ) genes of Saccharomyces cerevisiae. Previous studies showed that PAU induction requires the depletion of heme and is dependent upon the transcription factor Upc2. We have now identified additional factors required for PAU induction during hypoxia, including Hog1, a mitogen-activated protein kinase (MAPK) whose signaling pathway originates at the membrane. Our results have led to a model in which heme and ergosterol depletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 124 publications
(161 reference statements)
2
78
2
Order By: Relevance
“…It is notable in this respect that lipid metabolism is strongly regulated at the epigenetic level 79 , which is, through Zn-dependent HDACs, heavily dependent on zinc concentration. A similar hierarchy of shared control between regulators has been proposed before, for instance in membrane alterations caused by ergosterol and heme depletion 80 . While Hog1 has been the multifunctional protein shown in that study to confer cellular adaptation, it is interesting that Izh2 has been linked with both ergosterol metabolism and cellular response to hypoxia 16,55 .…”
Section: Discussionmentioning
confidence: 57%
“…It is notable in this respect that lipid metabolism is strongly regulated at the epigenetic level 79 , which is, through Zn-dependent HDACs, heavily dependent on zinc concentration. A similar hierarchy of shared control between regulators has been proposed before, for instance in membrane alterations caused by ergosterol and heme depletion 80 . While Hog1 has been the multifunctional protein shown in that study to confer cellular adaptation, it is interesting that Izh2 has been linked with both ergosterol metabolism and cellular response to hypoxia 16,55 .…”
Section: Discussionmentioning
confidence: 57%
“…Bahn et al reported that the phosphorylation of Hog1 MAPK activates downstream target genes to effect adaptation to environmental stressors (24). The Hog1 signaling pathway is, interestingly, also reported to be responsible for the maintenance of cell membrane/wall integrity (13,14). Thus, in our study, we sought to establish if the treatment of cells with aspirin and ibuprofen can cause membrane damage and, in turn, lead to activation of Hog1 MAPK.…”
Section: Resultsmentioning
confidence: 93%
“…In order to determine if our two test drugs could lead to stress induction, we performed a Hog1 mitogen-activated protein kinase (MAPK) Western blot assay (13,14) that was complemented with a phospho-p38 MAPK enzyme-linked immunosorbent assay (ELISA). For Western blot analysis, cultures were treated with 180 g/ml aspirin, 206 g/ml ibuprofen, 58,000 g/ml (1 M) sodium chloride (NaCl; Sigma-Aldrich, South Africa), or 34 g/ml (1 mM) hydrogen peroxide (H 2 O 2 ; Sigma-Aldrich, South Africa) for 20 min (grown at 30°C in YNB broth).…”
Section: Methodsmentioning
confidence: 99%
“…Similar results were obtained by comparing osmotolerant anaerobic strains to GPD1 overexpressing strains. Interestingly, Hickman et al (2011) also reported hypoxia-mediated activation of Hog1p and demonstrated that kinetics of Hog1p activation in response to hypoxia and osmotic stress are very different. Hog1p shows rapid transient activation in response to osmotic stress response as reported earlier, but it is activated slowly (over a period of 5 h) in response to hypoxia (Hickman et al, 2011).…”
Section: Osmoregulation and The General Response To Environmental Stressmentioning
confidence: 99%